State power and governance in early Imperial China: the collapse of the Qin Empire, 221-207 BCE - Tong, Chun Fung (SUNY series in Chinese philosophy and culture, 2024)
"Offers a new perspective on the Qin dynasty in early China and the reasons for its collapse"--